Enhancement of cancer specific delivery using ultrasound active bio-originated particles1. Issue 46 (11th June 2015) - Yoon, Young Il; Ju, Kook Yun; Cho, Hee-Sang; Yu, Kyeong Nam; Lee, Jae Jun; Ahn, Gook Jun; Lee, Soo-Hong; Cho, Myung Haing; Lee, Hak Jong; Lee, Jin-Kyu; Yoon, Tae-Jong
<x xml:space="preserve">Abstract</x> A bio-available microbubble, liposome, and Fe3+ chelated melanin nanoparticle complex with a dual ultrasound and T1-w magnetic resonance imaging modality has been synthesized for the specific targeting of cancer cells.